Phylogeny and morphological characters of Sinocarum filicinum (Apiaceae: Apioideae), a taxonomic revision - Gou, Wei; Xiao, Yan-Ping; Guo, Xian-Lin; Price, Megan; Jiang, Qiu-Ping; Zhou, Song-Dong; He, Xing-Jin (Phytotaxa, 2026)
The study reanalyzed the morphology (especially fruits) and phylogeny (based on nrITS and plastid DNA rpl16 and rps16 intron sequences) of S. filicinum and its related species aiming to resolve taxonomic uncertainties. The results showed that Meeboldia achilleifolia, M. delavayi, M. linearis, M. microloba and S. filicinum constitute a well-supported monophyly in nrITS and plastid DNA trees. We found that S. filicinum is distinct from other Sinocarum species including S. vaginatum, S. cruciatum and the type S. coloratum in all trees. Concern morphology, S. filicinum is more similar to Meeboldia species, rather than S. coloratum in plant height, fruit size, number of vallecular vittae and commissural vittae. The authors propose that S. filicinum be transferred to Meeboldia and be renamed as Meeboldia filicina (H.Wolff) W.Gou, Y.P.Xiao & X.J.He.